(untitled) (Vietnam Journal of Agriculture and Environment, 2024)
Heavy metal contamination in aquatic ecosystems poses a significant threat to both environmental health and human populations due to the persistent and toxic nature of these pollutants. This study focuses on the bioaccumulation of heavy metals (Zn, Cu, Pb, Cr, Cd) in Lanceolaria sp., a benthic invertebrate and examines the correlation between metal concentrations in the organism and sediments from the Cau River basin in Northern Vietnam. Sampling was conducted at 28 locations along the Cau River. The results indicate that metal accumulation in Lanceolaria sp. follows the order Zn > Cu > Pb > Cr > Cd, with average concentrations of 52.932, 19.343, 18.496, 7.549, 4.536 mg/kg dry weight, respectively. Chromium levels exceeded the Hong Kong standard at 10 of the 28 monitoring sites. Strong positive correlations were identified between sediment and organism concentrations for Cu, Pb, Zn and Cd (r = 0.40, p < 0.05). These findings highlight the potential of Lanceolaria sp. as an effective bioindicator for assessing heavy metal pollution in freshwater ecosystems.